Flutuação populacional e infestação de mosca-das-frutas (Diptera: Tephritidae) em função do sistema produtivo de goiaba - Duarte, Rogério T. [UNESP]; Galli, Júlio C. [UNESP]; Pazini, Wilson C. [UNESP]; Calore, Ricardo A. [UNESP] (Revista Brasileira de Ciencias Agrarias, 2013)
The knowledge about population fluctuation of fruit flies (Diptera: Tephritidae) is an important tool to be adopted in pest control. Thus, this research aimed to analyse the population fluctuation of adults of fruit flies and the infestation of larvae in fruits depending on the conventional and organic agricultural systems of guava production in the 2010/2011 harvest. For monitoring the adults of fruit flies, five yellow sticky traps were installed in each system. The infestation percentage and the calculation of the ratio number of larvae/number of fruits were determined at harvest by harvesting 10 mature fruits/plant, in ten plants, for each system. In organic system predominated Anastrepha spp., principally in the period when the fruits were ripening or ripe, represented by elevated infestation percentage, while the conventional system presented low population density of fruit flies, with reduced larvae infestation inside the fruits.
Population fluctuation and incidence of fruit flies (Diptera: Tephritidae) in different systems of guava production
Keywords: Insecta; Integrated pest management; Population monitoring; Psidium guajava L.; Tephritids